Dampak Burnout dan Workload Terhadap Kinerja Karyawan: Studi Kasus Pabrik Tahu Kadungora Kabupaten Garut - Siti Aisyah Nursyifa Arasyid; Husni Muharam; Fitrin Rawati Suganda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Employee performance is a crucial factor in determining the productivity and operational success of a company, including in the home industry sector such as the Kadungora Tofu Factory in Garut Regency. However, high physical work pressure and tight production targets can trigger burnout and excessive workload, which ultimately has an impact on decreased performance. This study aims to analyze the effect of burnout and workload on employee performance, both partially and simultaneously. This study uses a quantitative approach with a survey method by distributing questionnaires to 54 respondents from nine tofu factories in Kampung Bojong Bunggur, Kadungora. The analysis assistance technique used is multiple linear regression with SPSS version 20 software. The results of the study showed that burnout and workload simultaneously had a significant effect on employee performance with a contribution of 76.1%. Partially, both variables also showed a positive and significant effect, with workload being the dominant factor in influencing performance. These findings indicate the importance of saving workload and preventing work fatigue in increasing employee work effectiveness in the manual production sector.